Aluminium-12wt% silicon coating prepared by thermal spraying technique: Part 2 microstructure and properties - A. Yudee (2018)
At present, thermal spray technology has been widely used as an alternative method for wear protect-ion in materials by applying coated layer on an original worn surface. This research studied the thermal sprayed Al-12wt%Si coating prepared by flame spray technique. This material has been known as a candidate for wear resistance in particularly an automobile industry. In this research, the most suitable spraying condition had been achieved by a design of experiment which was 38 ft3/hr (1.026 m3/hr) of oxygen flow rate, 27 ft3/hr (0.729 m3/hr) of acetylene flow rate and 58 mm of spray distance. The as-sprayed coating had a hardness of 87.0±8.3 HV, thickness of 236.7±20.5 μm, percentage volume fraction of porosity of 14.99±1.63 and wear rate of 1.108×10-3± 0.001 mm3/m. Microstructure of the coating was also investigated.